2022
DOI: 10.1002/eqe.3634
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and numerical modeling of rocking cross laminated timber walls on a flexible foundation

Abstract: With recent developments of engineered wood products such as cross laminated timber, mass timber buildings in areas of high seismicity are becoming feasible and offer benefits such as faster construction and unique architectural features. It has also opened the door to creating seismically resilient lateral systems that sustain minor and reparable damage during large earthquakes. This paper presents a numerical modeling procedure for mass timber rocking wall lateral system with distributed spring elements to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Equating Equation ( 1) with the expression gives an effective length of the wall equal to the thickness of wall. It's important to mention here that several past studies have proposed an effective length of two times the wall thickness for CLT walls [7,11,16]. Results with one and two layers exhibited almost identical results in this study and are not shown here for brevity.…”
Section: Numerical Model Validationsupporting
confidence: 76%
See 4 more Smart Citations
“…Equating Equation ( 1) with the expression gives an effective length of the wall equal to the thickness of wall. It's important to mention here that several past studies have proposed an effective length of two times the wall thickness for CLT walls [7,11,16]. Results with one and two layers exhibited almost identical results in this study and are not shown here for brevity.…”
Section: Numerical Model Validationsupporting
confidence: 76%
“…The CLT panels in each wall were joined by five equally spaced Ushaped flexural plates along the height of the wall to provide a minimum energy dissipation ratio of 0.3. Modulus of elasticity and yielding stress of each U-shaped plate were 2x10 5 MPa and 414 MPa. Post-tensioning was provided by using four 19 mm bars in each wall with an average initial post-tensioning force equal to 40% of yield strength (53 KN for each bar).…”
Section: Case Study Structuresmentioning
confidence: 99%
See 3 more Smart Citations